Examining Al-Khazin's Influence on Tafsir Writing in Indonesia (A Study of 17th and 20th Century Tafsir) - Ela Sartika; Amin Amin (Journal Analytica Islamica, 2023)
This research is based on the opinion of Abdur Rauf Al-Fansuri and Bisri Musthafa who mentioned that the writing of the tafsir book takes reference sources from the Al-Khazin interpretation, even though these two tafsirs were born in different centuries. The purpose of this research is to see how much influence Al-Khazin has in writing tafsir, especially the 7th century and 20th century tafsir and in what way Al-Khazin influences his interpretation. This research uses the literature study method by analyzing several sources both primary and secondary. The result of this research is that Al-Khazin proved to have a considerable influence on the writing of Al-Mustafid Tarjuman's interpretation and Al-Ibriz's interpretation. this can be seen, taking interpretations of several aspects. The first, aspects of hadiths or narrations, although both interpretations tend to rarely include sanads in their entirety. Second, taking the asbab nuzul verse. Third, the aspect of the story of israiliyyat or the story of the previous prophet. In addition, there are similarities and differences in including Al-Khazin's interpretation in both interpretations such as both interpretations both use signs to strengthen their interpretation including the interpretation taken from Al-Khazin, the difference is that Al-Mustafid Tarjuman's interpretation provides a clear explanation if the interpretation takes from Al-Khazin's interpretation is different from Al-Ibriz's interpretation which does not clearly express Al-Khazin's interpretation in his interpretation Penelitian ini dilatar belakangi oleh pendapat Abdur Rauf Al-Fansuri dan Bisri Musthafa yang menyebutkan penulisan kitab tafsirnya mengambil sumber referensi dari tafsir Al-Khazin, padahal kedua tafsir ini lahir dalam abad yang berbeda. Tujuan penelitian ini untuk melihat seberapa besar pengaruh Al-Khazin dalam geliat penulisan tafsir khususnya tafsir Abad 7 dan abad 20 dan dalam hal apa Al-Khazin mempengaruhi penafsirannya. Penelitian ini menggunakan metode studi kepustakaan dengan menganalisis beberapa sumber baik primer maupun sekunder. Hasil dari penelitian ini adalah Al-Khazin terbukti memberikan pengaruh yang cukup besar terhadap penulisan Tafsir Tarjuman Al-Mustafid dan Tafsir Al-Ibriz. hal ini terlihat, pengambilan penafsiran terhadap beberapa aspek diantaranya yaitu pertama, aspek hadits atau riwayat walaupun kedua tafsir cenderung jarang memasukkan sanad secara utuh. kedua, pengambilan asbab nuzul ayat. ketiga, aspek kisah Israiliyyat ataupun kisah nabi terdahulu. selain itu, terdapat persamaan dan perbedaan dalam mencantumkan penafsiran Al-Khazin dalam kedua tafsirnya seperti kedua tafsir sama-sama menggunakan tanda untuk menguatkan penafsirannya termasuk penafsiran yang diambil dari Al-Khazin, perbedaannya yaitu Tafsir Tarjuman Al-Mustafid relatif memberikan penjelasan jelas jika penafsirannya mengambil dari Tafsir Al-Khazin berbeda dengan Tafsir Al-Ibriz yang tidak secara jelas mengungkapkan penafsiran Al-Khazin dalam tafsirnya.